Differential Phosphorylation of Akt and signaling in CD4+ T Cells in Pathogenic and Apathogenic SIV Infection - Stephenson, S T; Bostik, V; Bostik, P (Epidemiologie, mikrobiologie, imunologie, 2016)
Increased CD4+ T cell apoptosis and activation induced cell death (AICD) as a result of HIV infection in humans and SIV infection in Rhesus macaques (RM) is indicative of disease. Some non-human primate species naturally infected by SIV, such as African sooty mangabeys (SM), do not succumb to SIV despite high viral loads. Previously, we showed that mRNA levels of GSK-3β a kinase involved in T cell signaling, are significantly decreased in SIV+ RM compared to SIV+ SM. The current study confirms that expression of GSK-3β is decreased at the protein level in SIV+ RM. In addition, CD4+ T cells from SIV+ RM, but not other animals show an increase in both total Akt, a kinase directly interacting with GSK-3β and p-AktThr308 in response to stimulation via CD3/CD28, which is associated with an increase in apoptosis. Furthermore, the differences between the uninfected and pathogenically or non-pathogenically infected animals are not only species specific, but also T cell subset specific and that these trends correlate with AICD. This is one of few studies indicating the activity of Akt can be specific to only one phosphorylation site and may be linked to the differences in AICD and resistance to the lentivirus induced disease.
Keywords: protoonkogenní proteiny c-akt; fosforylace; CD4-pozitivní T-lymfocyty; zvířata; Simian Immunodeficiency Virus; Simian Acquired Immunodeficiency Syndrome; AIDS opičí; Proto-Oncogene Proteins c-akt; T cells - AIDS - Nonhuman primate - Akt - intracellular signaling.; Phosphorylation; virus opičí imunodeficience; CD4-Positive T-Lymphocytes; Macaca mulatta; Animals